The past - Hadley, Tessa 1956- (Vintage, 2015)
Over five novels and two collections of stories Tessa Hadley has earned a reputation as a fiction writer of remarkable gifts, and been compared with Elizabeth Bowen and Alice Munro. In her new novel three sisters and a brother meet up in their grandparents' old house for three long, hot summer weeks. The house is full of memories of their childhood and their past - their mother took them there when she left their father - but now they may have to sell it. And under the idyllic surface, there are tensions. Roland has come with his new wife and his sisters don't like her. Kasim, the twenty-year-old son of Alice's ex-boyfriend, makes plans to seduce Molly, Roland's teenage daughter. Fran's children uncover an ugly secret in a ruined cottage in the woods. Passion erupts where it's least expected, blasting the quiet self-possession of Harriet, the oldest sister. A way of life - bourgeois, literate, ritualised - winds down to its inevitable end. With uncanny precision and extraordinary sympathy, Tessa Hadley charts the squalls of lust and envy disrupting this ill-assorted house party, as well as the consolations of memory and affection, the beauty of the natural world, the shifting of history under the social surface. From the first page the reader is absorbed and enthralled, watching a superb craftsman at work ...
Keywords: Brothers and sisters -- Fiction; Families -- Fiction; Fiktionale Darstellung